Career Development Reviewed from Self-Efficacy on Life Insurance Employees - Karina Natalia; Diny Atrizka (Kusuma Negara Business School, 2020)
Career development has an impact on the progress of a company or organization. Therefore every company wants to strive to improve the career development of its employees. This study aimed to determine the relationship between self-efficacy and career development. In this study quantitative research methods are used and put forward a hypothesis namely that there was a positive correlation between self-efficacy and career development. A total of 187 agents of PT. Sequislife Life Insurance, Gatot Subroto branch, Medan which is the subject of this research. This Study used Product Moment correlation to analyzed data.. And the results of the study showed that the contribution given by the self-efficacy variable to career development was 26.7 percent and the rest 73.3 percent with a correlation coefficient of 0.517 and the relevant value of 0.000 (p <0.05). Then the conclusion was found that the hypothesis was accepted, namely there was a positive relationship between self-efficacy and career development.